2020
DOI: 10.1016/j.redox.2020.101739
|View full text |Cite
|
Sign up to set email alerts
|

Reductive stress promotes protein aggregation and impairs neurogenesis

Abstract: Redox homeostasis regulates key cellular signaling in both physiology and pathology. While perturbations result in shifting the redox homeostasis towards oxidative stress are well documented, the influence of reductive stress (RS) in neurodegenerative diseases and its mechanisms are unknown. Here, we postulate that a redox shift towards the reductive arm (through the activation of Nrf2 signaling) will damage neurons and impair neurogenesis. In proliferating and differentiating neuroblastoma (Neuro 2a/N2a) cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 59 publications
(50 reference statements)
0
15
0
Order By: Relevance
“…Reductive stress has been observed in many different disease conditions in a variety of organisms and cell types, all of which are associated with protein aggregation [ 26 , 46 , 56 , 57 ]. Organisms have evolved many pathways to degrade protein aggregates [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reductive stress has been observed in many different disease conditions in a variety of organisms and cell types, all of which are associated with protein aggregation [ 26 , 46 , 56 , 57 ]. Organisms have evolved many pathways to degrade protein aggregates [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…The current hypothesis for the underlying mechanism of reductive stress is that it is triggered by cytoplasmic protein aggregation ( Fig. 3 A) [ 25 , 57 ]. As an in vivo test of this hypothesis, an RNAi transgene against target of rapamycin ( TOR ) was expressed in larval body wall muscles with mutant LamC .…”
Section: Resultsmentioning
confidence: 99%
“…Damage from the excessive production of ROS is a well-known phenomenon; on the other hand, reductive stress may be even more harmful than oxidative stress through several mechanisms, such as the disruption of signaling functions of ROS, the induction of ROS generation, the perturbation of cell metabolism, the inhibition of protein disulfide formation and the impairment of the proteostasis network [ 167 ]. Evidence of this is shown in a recent work where Narasimhan et al have demonstrated that activation of the Nrf2-antioxidant signaling under basal-setting declines ROS leading to a reductive-redox state and subsequent ER stress, protein aggregation and proteotoxicity in neuroblastoma cells [ 168 ]. However, the beneficial effects of reductive stress have been also described, e.g., mitochondrial oxidation induced by NAC stimulates mitochondrial biogenesis through a mitohormesis mechanism, leading to an increased mitochondrial content and an improvement of antioxidant capacities in myoblasts [ 161 ].…”
Section: Pro-gsh Molecules: Oxidative Stress Inhibitors or Reductimentioning
confidence: 99%
“…It is known that NAC not only has a strong antioxidant effect but is also a potential inducer of reductive stress in cells [ 37 ]. Reductive stress, which is the counterpart to oxidative stress, is defined as an abnormal increase in the level of intracellular reducing equivalents in the form of NADH, NADPH, and GSH that results in various disturbances of cell metabolism, including ER stress and protein aggregation [ 38 , 39 , 40 ]. We hypothesized that excessive elimination of intracellular oxidants in MSCs caused by the action of Tempol and resveratrol could disrupt the redox balance and, similar to NAC, induce reductive stress.…”
Section: Resultsmentioning
confidence: 99%
“…Under these conditions, the redox equilibrium is shifted towards the reduction processes, i.e., in the direction opposite to oxidative stress. Since the maintenance of physiological redox homeostasis in the ER is critical for the functioning of enzymes responsible for proper protein folding, reductive stress can lead to protein misfolding and ER stress induction [ 39 ]. In our experiments, the expression pattern of the ER stress marker genes turned out to be very similar when MSCs were treated with both high concentrations of AOs (Tempol, resveratrol, and NAC) and DTT a classical inducer of reductive stress.…”
Section: Discussionmentioning
confidence: 99%